Perceived support and intention to leave: the effect on new educators / Mazida Ismail, Muruga Chinniah and Nani Shuhada Sehat - Ismail, Mazida; Chinniah, Muruga; Sehat, Nani Shuhada (Research Management Institute (RMI), 2013)
The escalation of unemployed graduate’s phenomena not only is a local issue but have become global. Clark (2009) reported that graduate unemployment in UK has soared 44 per cent in a year and is at its highest for more than a decade while 81,046 Malaysian graduates registered on labour exchange seeking job (Electronic Labour Exchange, Ministry of Human Resources, 2009). Through a lot of discussion and research done by researcher, academicians and authorities, half of the findings pointing back to education policies and educators. Thus in order to overcome this problem from becoming huge, ones must go back to the root factor that is the educators. As a human, certain individual needs must be satisfied first before they could deliver their knowledge appropriately. These include need for belongingness that contains affection and interaction with other people (eg. Organization, supervisor and co-worker) and esteem need that are gained through recognition. Nevertheless, the different workplace expectations brought by the new generation (McShane & Von Glinow, 2009) might give a different connotation to this situation. Therefore a study on the relationship of perceived support and intention to leave among new academician will be conducted. The purpose of this study are to examine the direct relationship between perceived support and intention to leave and then examine which type of support (namely organisational, supervisor and co-worker support) give the most influence to intention to leave. Data on 113 permanent new lecturers (served less than 3 years) in UiTM Segamat will be obtained using questionnaires and recorded and further analyse using SPSS Version 17. It is assumed that perceived support and intention to leave has a direct negative relationship and supervisor support is the most influential factor of intention to leave.